Highly sensitive volatile organic compounds vapour measurements using a long period grating optical fibre sensor coated with metal organic framework ZIF-8 - Hromadka, Jiri; Tokay, Begum; Correia, Ricardo; Morgan, Stephen P.; Korposh, Sergiy (Elsevier, 2018)
An optical fibre long period grating (LPG) based volatile organic compound (VOC) sensor coated with ZIF-8, a material from the zeolite imidazolate framework (ZIF) family, functional coating is presented. ZIF-8 film was deposited onto the surface of the LPG using an in-situ crystallization technique by mixing freshly prepared 12.5 mM zinc nitrate hexahydrate and 25 mM 2-metyl-imidazole solutions in methanol. A concentration specific response to acetone, ethanol and methanol vapour was obtained over the high concentration range up to tens thousands ppm. The LPG based sensor works at phase-matching turning point (PMTP) and such operates at the highest sensitivity. A novel approach for the data analysis based on the measurement of the bandwidth of the U-shaped attenuation band of the LPG is introduced. The optimized sensor shows a sensitivity of 0.015 ± 0.001 and 0.018 ± 0.0015 nm/ppm and limit of detection (LOD) of 6.67 and 5.56 ppm for acetone and ethanol respectively.